Putting virtual theatre models to work: 'virtual praxis' for performance research in theatre history. Issue 1 (3rd April 2021) - Bollen, Jonathan; Holledge, Julie; Tompkins, Joanne
ABSTRACT: So much time, research and effort are expended in accurately developing virtual models of theatres, but what happens when they are completed? It is not automatically clear how one uses a virtual model for research to generate new knowledge about performance. Our research has recreated a series of theatres, which no longer exist, in virtual form in order to visualise elements of performance and the social relations that shape and are shaped by a theatre venue. These international theatres include the Rose in London from the late 1500s, the Bergen Theatre from 1850, the Queen's Theatre in Adelaide from 1841, an itinerant bamboo theatre for performing Cantonese opera along the Pearl River Delta in China and a tent version used to house the same form in the goldfields of Victoria, and the showroom at the Stardust Hotel in Las Vegas built in the late 1950s. This article has two aspects: the first outlines our work with actors in workshops to explore how the spatial dynamics of the models can inform knowledge of acting traditions and audience response appropriate to each venue. The second explores some of the challenges of installing era-specific lighting and sound technology in several of the venue models.